2018
DOI: 10.1111/cup.13093
|View full text |Cite
|
Sign up to set email alerts
|

Contiguous verrucous proliferations in syringocystadenoma papilliferum: A retrospective analysis with additional evaluation via mutation‐specific BRAFV600E immunohistochemistry

Abstract: Overall, these findings suggest that contiguous verrucous proliferations in SCAP are common. Both components of the neoplasm may express the BRAFV600E mutation, which is suggestive of a common origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…BRAF V600E mutation has been recently found in more than 55% of s‐SCAP cases, expanding the spectrum of BRAF‐related cutaneous neoplasms . It is plausible that the immunohistochemical expression of BRAF VE1 in the accompanying squamous proliferation in our cases and in some published SCAP may correspond to a copy‐number amplification of the BRAF V600E alleles, as is the case with concurrent HRAS mutation and amplification in a minority subset of Spitz nevi, including those arising within nevus spilus . In our cases, not only was immunoreactivity found in the glandular and in the squamous constituents of the two lesions studied, but also after macro‐dissection and subsequent repetition of the molecular study, BRAF V600E mutation was detected in each of the lesional components separately, reinforcing the pathogenic role of this genetic alteration not only in the SCAP but also in the associated warty proliferation.…”
Section: Discussionsupporting
confidence: 54%
“…BRAF V600E mutation has been recently found in more than 55% of s‐SCAP cases, expanding the spectrum of BRAF‐related cutaneous neoplasms . It is plausible that the immunohistochemical expression of BRAF VE1 in the accompanying squamous proliferation in our cases and in some published SCAP may correspond to a copy‐number amplification of the BRAF V600E alleles, as is the case with concurrent HRAS mutation and amplification in a minority subset of Spitz nevi, including those arising within nevus spilus . In our cases, not only was immunoreactivity found in the glandular and in the squamous constituents of the two lesions studied, but also after macro‐dissection and subsequent repetition of the molecular study, BRAF V600E mutation was detected in each of the lesional components separately, reinforcing the pathogenic role of this genetic alteration not only in the SCAP but also in the associated warty proliferation.…”
Section: Discussionsupporting
confidence: 54%
“…Among 18 cases of SCAP with such a morphology described in the literature, the most common location was the cheek (16.7%), scalp (16.7%), and lower extremity (16.7%) followed by the buttock (11.1%), neck (11.1%), vulva (5.5%), sacral area (5.5%), back (5.5%), аreola (5.5%), and eyelid (5.5%). 2,[19][20][21][22][23][24][25] The cause of such contiguous verrucous proliferations in SCAP is unclear. Some authors have suggested a possible role of HPV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al reported a higher incidence (9/12, 75% cases) of contiguous squamous proliferations. 1 Konstantinova et al studied syringocystadenoma papilliferum of anogenital region where 10/16 cases (62.5%) had contiguous squamous proliferations. 2 The clinical appearance of the lesion is unable to predict underlying contiguous squamous proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Syringocystadenoma papilliferum is a benign adnexal neoplasm derived from pluripotent cells. 1 Rarely, contiguous squamous proliferations appear in syringocystadenoma papilliferum.…”
Section: Introductionmentioning
confidence: 99%